Postovulatory maternal transcriptome in Atlantic salmon and its relation to developmental potential of embryos - Bizuayehu, Teshome Tilahun; Mommens, Maren; Meenakshi Sundaram, Arvind Yegambaram; Dhanasiri, Anusha Krishanthi Shyama; Babiak, Igor (BMC Genomics, 2019)
publishedVersion